Ameloblastoma: A multicentric study - Kittipong Dhanuthai (2018)
Objective. The objective of this study was to supplement the current ameloblastoma database by reporting the clinicopathologic features of ameloblastoma from Asia and North America. Materials and Methods. Biopsy records of the participating institutes were reviewed for lesions diagnosed as ameloblastoma during the years 1993 to 2009. Slides were reclassified according to the World Health Organization Classification of Odontogenic Tumors in 2005. Clinical information and radiographic features were collected and analyzed. Results. The mean age of the patients ± SD was 38.27 ± 17.78 years; 662 patients (51.36%) were men. Mandible (84.26%) outnumbered maxilla and other locations combined in all countries. The number of multilocular radiolucencies (43.40%) was comparable with that of unilocular radiolucencies (42.04%). Follicular pattern was the most common histopathologic pattern (27.70%), followed by plexiform (21.10%) and unicystic pattern (20.71%), respectively. Conclusions. The clinicopathologic features of ameloblastomas in the present study show some similarities with previous studies; however, minor differences exist. © 2012 Elsevier Inc. All rights reserved.